Is appropriation a useful category for scholarship on religion? Concluding remarks - Bucar, Liz (Approaching Religion, 2023)
Concluding remarks for the special issue of Approaching Religion, ‘Appropriation as a Perspective and Topic in the Study of Religion and Spirituality’.